Diagnostic and therapeutic features of refractive amblyopia in children with cerebral palsy (Herald of the National Children's Medical Center, 2025)
Background. To identify the clinical and functional characteristics of refractive amblyopia in children with cerebral palsy (CP) and to evaluate the effectiveness of a comprehensive ophthalmological correction program combining traditional and adapted therapeutic methods.Materials and methods. A prospective clinical study included 39 children (78 eyes) aged 3 to 12 years diagnosed with CP and confirmed refractive amblyopia. Visual impairment was assessed using adapted diagnostic techniques that took into account motor and cognitive limitations. Treatment included individually prescribed optical correction, occlusion therapy, hardware-based methods (Amblyotron), as well as speech and psychological support.Results. Following a six-month course of therapy, a statistically significant improvement in visual acuity (from 0.31 to 0.47; p
Keywords: cerebral palsy; refractive amblyopia; visual function; ophthalmologic rehabilitation